Anti‐Friction MSCs Delivery System Improves the Therapy for Severe Osteoarthritis. Issue 52 (24th October 2021) - Yan, Xin; Yang, Bo; Chen, Yourong; Song, Yifan; Ye, Jing; Pan, Yufan; Zhou, Bini; Wang, Yuqing; Mao, Fengbiao; Dong, Yuanchen; Liu, Dongsheng; Yu, Jiakuo
Abstract: Osteoarthritis (OA) is a musculoskeletal disorder disease affecting about 500 million people worldwide and mesenchymal sem cells (MSCs) therapy has been demonstrated as a potential strategy to treat OA. However, the shear forces during direct injection and the harsher shear condition of OA environments would lead to significant cell damage and inhibit the therapeutic efficacy. Herein, DNA supramolecular hydrogel has been applied as delivering material for MSCs to treat severe OA model, which perform extraordinary protection in MSCs against the shear force both in vitro and in vivo. It is demonstrated that the DNA supramolecular hydrogel can promote formation of quality cartilage, reduce osteophyte, and normalize subchondral bone under the high friction condition of OA, whose molecular mechanisms underlying therapeutic effects are also investigated. It can be anticipated that DNA supramolecular hydrogel would be a promising cell delivery system for multiple potential MSCs therapy. Abstract : A DNA supramolecular hydrogel is employed as a carrier for bone marrow mesenchymal stem cells (BMSCs) to treat osteoarthritis (OA). Compared with current clinical strategies, the DNA supramolecular hydrogel can significantly improve the vitality of BMSCs during delivery, and provide cells with long‐term antifriction protection, excellent permeability, 3D support, and 3D microenvironment of cell proliferation and differentiation, ultimately enhancing the therapeutic effect of BMSCs.